Solubility dynamic of methyl yellow and carbon black in microemulsions and lamellar liquid crystal of water, non ionic surfactants and cyclohexane system. Issue 1 (January 2016) - Amran, A; Harfianto, R; Dewi, W Y; Beri, D; Putra, A
Abstract: Solubility dynamics of methyl yellow and carbon black in microemulsions and liquid crystals of water, non-ionic surfactants and cyclohexane system, have been investigated. Actually, solubility dynamics of these dyes both in microemulsion (w/o microemulsions) and the lamellar liquid crystal (LLC) were strongly related to the chemical composition, nature and characteristics of microemulsions and the lamellar liquid crystals.